Omega-3 and vitamin D supplementation to reduce recidivism: a pilot study - Raine, Adrian (2023)
Objectives: While three randomized controlled trials (RCTs) have been conducted using omega-3 supplementation on prison populations, none have examined effects on recidivism. This study presents pilot findings on recidivism rates following omega-3 and vitamin D supplementation. Methods: Young offenders (N = 145) were randomized into 3 groups: omega-3/vitamin D supplementation (N = 48), placebo (N = 46), and treatment-as-usual controls (N = 51). One-, two-, and three-year recidivism rates were calculated. Results: The omega-3 group showed non-significantly reduced recidivism rates compared to both control groups in all three years. Three-year recidivism reduction effect sizes were as follows: omega-3 versus controls (d =.18) and omega-3 versus placebo (d =.17). Conclusions: A future study with a sample size of 237 would have a power of.80 to detect these effect sizes. These pilot data suggest that omega-3 and vitamin D supplementation, a simple and relatively cheap health intervention, could reduce 3-year recidivism by 16.6%.